Organic Anion Transporting Polypeptide‐Mediated Transport of, and Inhibition by, Asunaprevir, an Inhibitor of Hepatitis C Virus NS3 Protease. Issue 2 (20th December 2014) - Eley, T; Han, Y‐H; Huang, S‐P; He, B; Li, W; Bedford, W; Stonier, M; Gardiner, D; Sims, K; Rodrigues, AD; Bertz, RJ
<x xml:space="preserve">Abstract</x> Asunaprevir (ASV), an investigational, highly protein‐bound inhibitor of hepatitis C virus NS3 protease, shows considerable hepatic compartmentalization in animal models. Preclinical data showed ASV inhibition of human OATP1B1 (IC50 = 0.3 μM), OATP2B1 (0.27 μM), and, to a lesser extent OATP1B3 (3.0 μM), confirmed by modest (<2‐fold) clinical elevations in rosuvastatin exposure with concomitant ASV. Although no significant OATP transport of ASV was observed in vitro at standard micromolar assay concentrations, clinical coadministration of ASV with a single dose of the OATP inhibitor rifampin gave large, variable increases in ASV plasma Cmax (21‐fold mean) and AUCinf (15‐fold mean), consistent with reduced hepatic uptake. In vitro reevaluation at therapeutically relevant low‐nanomolar concentrations of unbound ASV showed active, saturable human hepatocyte uptake (Km = 0.685 μM) and rifampin‐reversible transport by OATP1B1 and OATP2B1, but not OATP1B3. At therapeutically relevant concentrations, ASV is therefore a sensitive substrate for, and weak inhibitor of, human OATP1B1, 1B3 and 2B1.